'Autism itself actually isn't a disability': Negotiating a 'normal' versus 'abnormal' autistic identity. (14th May 2015) - Lester, Jessica; Karim, Khalid; O'Reilly, Michelle
Abstract : The opposing positions of the social model of disability and the biomedical framework of impairment have created tensions regarding what constitutes 'normality'. In this article, we drew upon focus group data of parents, professionals, and people with autism, to explore how the dilemmatic tensions of normality and abnormality and of disability and ability were managed. Our findings illustrate how the boundaries of normality in relation to autism are blurred, as well as how the autistic identity is fluid. The members of the focus group invoked their epistemic rights to assert their positions and delicately considered the limitations of the rhetoric of cure. Our findings have implications for professionals working with families of children with autism, specifically as they aim to maintain a balance between providing sufficient support and not being intrusive, and we show how a medical sociology can facilitate an understanding of autism as a social category.